The role of interaction between low molecular weight neutral organic compounds and a polyamide RO membrane in the rejection mechanism. Issue 26 (21st April 2020) - Zhang, Muxue; Breitner, Lauren; Howe, Kerry J.; Minakata, Daisuke
Abstract : Reverse osmosis (RO) is a membrane technology that separates dissolved species from water. Abstract : Reverse osmosis (RO) is a membrane technology that separates dissolved species from water. RO has been applied for the removal of chemical contaminants from water and is employed in wastewater reclamation to provide an additional barrier to improve the removal of trace organic contaminants. The presence of a wide variety of influent chemical contaminants and the insufficient rejection of low molecular weight neutral chemicals by RO calls for the need to develop a comprehensive model that predicts the rejection of various chemicals in RO. Yet the role of the interaction between neutral organic compounds and a RO membrane, and how the functional groups of organic compounds affect the interaction have not been fully elucidated. In this study, we first constructed a molecular model for a reference polyamide (PA) membrane. We then investigated the impact of explicit water molecules and PA membrane functionality on the membrane structure using quantum mechanical calculations. We examined solvent–membrane interactions and then solvent–membrane–solute interactions using two neutral test solutes, arsenic and boron, by comparing the theoretically calculated aqueous-phase free energies of interaction with their experimental values. Finally, the validated PA membrane model was used to calculate the free energies of interaction for a wide variety of organic compounds such as haloalkanes, haloalkenes, alkylbenzenes and halobenzenes, which correlated with the experimentally obtained mass transfer coefficients. The correlation indicates that the interaction between organic compounds and PA membranes plays a critical role in the rejection mechanism.